Deliberação moral da enfermeira frente aos problemas éticos vivenciados no acolhimento com classificação de risco - Silva, Edneide Barbosa da (2025)
The risk classification is a device that proposes organizing urgent and emergency care based on criteria of clinical severity and not in order of arrival, as well as making users and family members aware that care will be in order of urgency and waiting time for their case. While Moral Deliberation is understood as an evaluation method to facilitate effective decisionmaking in the face of an ethical problem experienced in a work environment. This study aimed to understand the moral deliberation of nurses in the face of ethical problems experienced in Reception with Risk Classification in an emergency care unit. Qualitative study based on the theoretical-methodological framework of deliberative bioethics proposed by Diego Gracia. The research project was approved by the Ethics and Research Committee of the State University of Feira de Santana, under opinion no. 6760052. Eight (8) nurses who work in a polyclinic in the interior of Bahia participated in the study. Data were collected from May to August 2024, through semi-structured and recorded interviews after the participants' authorization. The interviews took an average of 40 minutes. Firstly, the content analysis proposed by Bardin was carried out. In the second moment, a vignette was applied with an ethical problem experienced by the researcher in the work environment, related to risk classification in an emergency care unit. In the first moment of analysis, two categories were found: Risk classification in emergency care and Experience of ethical problems in reception and risk classification. The result revealed that the user is initially attended to by the unit's reception, and seeks to find out about the main complaint and the reason that led to seeking care. They understand that ethical problems may arise during this process, such as conflicts with users and family members. The method of deliberative bioethics enabled reflection on the clinical case and demonstrates its importance, just like this case, it is clear that ethical problems can emerge in the nurse's work environment in the context of emergency care during Reception with Risk Classification. Faced with the ethical problems experienced by nurses when classifying risks, nurses' moral deliberation is necessary. As a product of this study, the Manual on Reception with Risk Classification in Emergency Care Units was created with the aim of guiding nurses in the planning and execution of reception activities in services through decision-making as an integral part of their work process.